THE FACTORS EFFECT ON THE QUALITY OF FINANCIAL STATEMENTS - Inneke Agustina; Emmy Indrayani (Jurnal Ilmiah Ekonomi Bisnis, 2021)
Indications of fraud or errors in financial statements cause the information presented to be unreliable, irrelevant, incomparable, and inapplicable. Unqualifiedfinancial statements cannot be used by various parties, especially in corporate decision-making. The quality of financial statements can be created through the application of information technology and internal controls which are effective and efficient. This study aims to analyze how the effect of the accounting information system and internal control system in the Indonesian Television PublicBroadcasting Institute (LPP TVRI). The independent variables used are the Accounting Information System and the Internal Control System. Meanwhile, the dependent variable used is the Quality of Financial Statements. The data were obtained using a questionnaire and analyzed using the Partial Least Square (PLS)method. The sample used in this study was 36 employees who work in the Budget, Accounting and Taxation, and Internal Audit, divisions. The results of this study indicate that the accounting information system has a significant effect on the quality of financial statements. Meanwhile, the internal control system has no significant effect on the quality of financial statements.